PENGUKURAN KINERJA INSTALASI FARMASI RUMAH SAKIT DAERAH LIUN KENDAGE TAHUNA BERDASARKAN PERSPEKTIF CUSTOMER DAN LEARNING AND GROWTH - Gayatri Citraningtyas; Deby Afriani Mpila; Mariana Gagola (Jurnal Ilmiah Manuntung, 2020)
This recent day hospital facing a competitive competition, and high expectation of health services from public. Thus the hospital have to fix and improve public health services quality. There was a need to evaluate Pharmacy Installation performance, if the hospital already work in line with the vision, mission, and goal of the organization. The objectives of this research was to performance measurement of Pharmacy Installation at RSD Liun Kendage Tahuna using balanced scorecard (BSC) method from customer perspective and learning and growth perspective. Research design used in this study was descriptive evaluation with prospective data collection. Qualitative data was a inteview with head of Pharmacy Installation, although quantitative data were an observation, questionnaire and administration report. The result of performance measurement from customer perspective showed Ikj value were -0,43 (negative index), which means there were a gap between the reality and expectation on health services that delivered. Patient growth level increased from 92,3 % in 2016; 94,5% in 2017; and 95,3% in 2018. Performance measurement from learning and growth perspective showed average value 2,85 for employee spirit (high category), and productivity were 78,64% (good category). The conclusion were Pharmacy Installation of RSD Liun Kendage Tahuna already showed a good performance, although there were a need to make an improvement on customer satisfaction.